Uma análise da influência da promoção de vendas de desconto na intenção de compra do consumidor e os efeitos moderadores da atratividade - Santini, Fernando de Oliveira (2013)
This study is aimed at examining the influence of discount sales promotion on consumer s purchase intention, and also the moderator effects of promotion attractiveness on the relations between intention of purchasing a discount product and the personal impulsive attributes of and the hedonic and financial risk perceptions by consumer. On this purpose, an experiment was performed involving 613 students in a School of Management. The hypotheses established were that a discount promotional product would relate positively to both the personal impulsive attribute and the hedonic perception of the promotional product, as well as negatively to the perception of financial risk associated to this product. A positive moderation effected of the attractiveness of the discount promotion on these referred relations was also expected. Results have partly corroborated the hypotheses, pointing to positive influence of personal impulsive attributes and hedonic perception on discount promotional product purchasing, and also to a negative association between purchasing intention and the perception of financial risk associated to the discount product. As to the moderator effects, the proposed relations were not confirmed, since the effect of attractiveness regarding both personal impulsive attributes and hedonic perception of the product was negative. It was not found a moderator effect of attractiveness on the association between intention of purchasing the discount promotional product and the perception of financial risk.